MANAGEMENT OF SCLEROTINIA WHITE ROT OF BEANS WITH ANTAGONISTIC MICROORGANISMS - Basheer A. Alsum; Mohamed Elsheshtawi; Maged T. Elkahky; Abdallah M. Elgorban; Marwah M. Bakri; Manal M. Alkhulafi (Journal of Animal and Plant Sciences, 2017)
In the present study, antagonistic activity of locally isolated bio agents including five fungi and three bacteria was evaluated against Sclerotinia sclerotiorum (Lib.) de Bary casual of white rot of snap beans. All tested biocontrol agents were able to inhibit radial growth and sclerotia viability in dual culture assay. Trichoderma hamatum (Bonorden) Bainier was the most effective agent in suppressing the mycelial growth of S. sclerotiorum by 93% compared to control. Whereas, tested isolates of Trichoderma viride Pers and Coniothyrium minitans Campbell were able to completely deactivating all treated sclerotia. In field trial, same isolates were tested in comparison of other commercial bio products. Naturally infested soil with S. sclerotiorum treated with local isolated bio agents as well as some commercial bio agents.  Local isolate of C. minitans was the most effective in reducing disease incidence and the disease severity by 94.6% living plants (5.4 % mortality) and 13.0, respectively. Trichoderma hamatum and Contans® (commercial product C. minitans) also minimized disease severity by 14 and 16.2%, respectively when compared to untreated control. Among tested bacterial bicontrol agents, Pseudomonas fluoroscens was the best in reducing disease severity by 21.3% compared to controls. Yield data showed that Trichoderma hamatum increased total yield (10.485 ton/ha) Conversely, C. minitans was the best in increasing quality of yield in terms of exportable yield that giving 9.729 ton/ha.
Keywords: Coniothyrium minitans; white rot; low tunnel; beans